Rate type silicon-carbon material as well as preparation method and application thereof

By refining and granular technology, the multiplier -type silicon carbon material is solved by the problem of poor performance of the existing silicon carbon material granules, and the negative electrode material of the lithium -ion battery with high magnification performance and safety and stability.

CN119340371APending Publication Date: 2025-01-21JINGHE NEW TOWN SHAANXI COAL TECH RES INST NEW ENERGY MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411534083.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The particle morphology of existing vapor-deposited silicon-carbon materials is irregular, resulting in poor rate performance, limiting their application in lithium-ion battery anode materials.

Method used

Through the method of refining carbon particles, the secondary granular ballization and activation of pores, the surface of the surface is smooth, angular -free, and sedimentation of silicon nanoparticles in its pores to form a multiplier silicon carbon material.

Benefits of technology

It achieves high rate performance and safety and stability, avoids tip discharge phenomena, and increases the compaction density of the material and the contact area between active material particles, enhancing the rate cycle and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340371A_ABST
    Figure CN119340371A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multiplying power type silicon-carbon material, which comprises the following steps: crushing a carbon precursor into carbon powder, mixing the carbon powder and a dispersing agent, adding the mixture into ethanol, stirring, grinding for the first time to form an emulsion, adding a coating agent into the emulsion, grinding for the second time, spraying and granulating to obtain an intermediate product, and drying to obtain the multiplying power type silicon-carbon material. Carrying out primary calcination on the intermediate product to form spherical sunken carbon powder, mixing the spherical sunken carbon powder with alkali, carrying out secondary calcination, washing and drying to obtain a carbon skeleton, putting the carbon skeleton into a fluidized bed, introducing silicon source gas into the fluidized bed, carrying out heat preservation at 400-700 DEG C for 1-6 hours, switching the silicon source gas into organic gas source gas, and carrying out heat preservation at 400-700 DEG C for 1-6 hours; keeping the temperature at 400-800 DEG C for 2-6 hours to obtain a multiplying power type silicon carbon material; the invention further discloses the multiplying power type silicon carbon material and application of the multiplying power type silicon carbon material as a negative electrode of a lithium ion battery, and the multiplying power type silicon carbon material is smooth and flat in particle surface, has circular and annular special morphology and is free of edges and corners.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon-carbon material preparation methods, and relates to a method for preparing a rate-type silicon-carbon material, the rate-type silicon-carbon material, and the application of the rate-type silicon-carbon material. Background Art

[0002] The rate characteristics of lithium-ion batteries are very important. Good rate characteristics mean that lithium-ion batteries can maintain high energy output and absorption speed at high rates without losing too much energy or causing battery overheating due to high rates. With the rapid development of digital information appliances and electric vehicles, consumers have put forward higher requirements for the rate performance of lithium-ion batteries.

[0003] Negative electrode material is one of the important raw materials of lithium-ion batteries. It plays the role of energy storage and release, and affects the initial efficiency, cycle performance, and rate performance of lithium-ion batteries. At present, vapor-deposited silicon-carbon material is usually used as the negative electrode material of lithium-ion batteries. Vapor-deposited silicon-carbon material has excellent reversible capacity, cycle and expansion performance, but the particle morphology of vapor-deposited silicon-carbon material is irregular, the convex surface of the particles is prone to tip discharge, and the particles of the material are prone to breakage when rolled, resulting in poor rate performance, which limits the further application of this material. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a rate-type silicon-carbon material, which solves the problem of irregular particle morphology of the silicon-carbon material in the prior art.

[0005] A second object of the present invention is to provide a rate-type silicon-carbon material.

[0006] The third object of the present invention is to provide an application of rate-type silicon-carbon material.

[0007] The first technical solution adopted by the present invention is a method for preparing a rate-type silicon-carbon material, comprising the following steps: Step 1: crushing the carbon precursor into carbon powder, mixing the carbon powder and the dispersant, adding them into ethanol, stirring, and grinding for the first time to form an emulsion; Step 2: adding a coating agent to the emulsion for a second grinding and spray granulation to obtain an intermediate product; Step 3: calcining the intermediate product for the first time to form spherical concave carbon powder; Step 4: Mix the spherical concave carbon powder and alkali, perform a second calcination, wash, and dry to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing silicon source gas into the fluidized bed, and keeping the temperature at 400° C.-700° C. for 1 h-6 h; Step 6: Switch the silicon source gas to an organic source gas, keep the temperature at 400°C-800°C for 2h-6h, and obtain a rate-type silicon-carbon material.

[0008] The first technical solution of the present invention is also characterized in that: The first grinding method is to pump the stirred product into a sand mill through a peristaltic pump for liquid phase grinding, and the second grinding method is to grind the mixture of the emulsion and the coating agent in a sand mill for liquid phase grinding.

[0009] The carbon precursor is one of biomass carbon, resin carbon or coke. The pulverizing method is to pulverize the carbon precursor into carbon powder with a particle size of 2μm-15μm through a jet mill. The dispersant is one or more of stearic acid, PVP, oleic acid, ricinoleic acid or octanoic acid. The carbon powder and the dispersant are mixed in a mass ratio of 10-100:1. After the carbon powder and the dispersant are mixed, they are added to ethanol so that the mass proportion of the carbon powder is 5%-30%. The first grinding time is 1h-6h.

[0010] The coating agent is one or more of petroleum asphalt, coal asphalt or emulsified asphalt. The mass of the added coating agent is 10%-100% of the mass of the carbon powder. The second grinding time is 0.5h-3h.

[0011] The first calcination and the second calcination are both carried out in a tubular furnace in a nitrogen atmosphere. The first calcination is carried out at 300°C-600°C for 0.5h-4h, and the second calcination is carried out at 700°C-900°C for 0.5h-4h.

[0012] The alkali is sodium hydroxide or potassium hydroxide, the intermediate product and the alkali are mixed in a mass ratio of 1:1-4, the washing method is acid washing with 1 mol / L hydrochloric acid, ethanol washing, and multiple deionized water washings until neutral, and the drying method is drying in an oven.

[0013] The silicon source gas is one of monosilane, disilane, trisilane or alkyl halide, and the flow rate of the silicon source gas is 0.5L / min-5L / min.

[0014] The organic gas source is one of acetylene, propane, cyclohexane, methane or benzene, and the flow rate of the organic gas source is 0.5L / min-5L / min.

[0015] The second technical solution adopted by the present invention is to obtain a rate-type silicon-carbon material by using a method for preparing a rate-type silicon-carbon material.

[0016] The third technical solution adopted by the present invention is the application of rate-type silicon-carbon material as the negative electrode of a lithium-ion battery.

[0017] The beneficial effects of the present invention are: The present invention prepares a carbon skeleton with a smooth surface and no edges and corners through primary carbon particle refinement, secondary granulation and spheroidization and activation pore formation, and precipitates gas into silicon nanoparticles dispersed in the pores of the carbon skeleton through high-temperature pyrolysis to prepare a silicon-carbon material with high rate performance. The method of primary particle refinement and secondary granulation and spheroidization solves the problem of difficult carbon skeleton shaping, and prepares a round carbon skeleton at a relatively low cost, which is not only conducive to the uniformity in the subsequent activation pore formation and silicon particle deposition process, but also reduces the puncture and breakage phenomenon when particles are squeezed against each other during the preparation process, and electrons are not easy to gather during the charge and discharge process, so that when it is applied to the negative electrode material of a lithium ion battery, it not only has high rate performance, but also ensures safety and stability. Compared with traditional silicon-carbon negative electrode materials, the rate-type silicon-carbon material prepared by the present invention has a smooth and round surface, and some particles are concave, which not only avoids the tip discharge phenomenon, but also improves the compaction density of the material, increases the contact area between active material particles, and is beneficial to the rate cycle performance and safety and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a scanning electron microscope image of Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of coconut shell gas phase silicon carbon; Figure 3 This is a scanning electron microscope image of super carbon gas phase silicon carbon; Figure 4 This is a cycle test data diagram of the assembled full battery of Example 1, coconut shell gas phase silicon carbon, and super carbon gas phase silicon carbon at a discharge rate of 0.5C and a charge rate of 1C; Figure 5 This is a data chart of rate charging test of assembled full batteries of Example 1, coconut shell vapor silicon carbon, and super carbon vapor silicon carbon. DETAILED DESCRIPTION

[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0020] A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: crushing a carbon precursor into carbon powder with a particle size of 2μm-15μm by a jet mill, wherein the carbon precursor is one of biomass carbon, resin carbon or coke, mixing the carbon powder and dispersant in a mass ratio of 10-100:1, adding the mixture to ethanol so that the carbon powder accounts for 5%-30% by mass, and stirring the mixture, wherein the dispersant is one or more of stearic acid, PVP, oleic acid, ricinoleic acid or n-octanoic acid, and pumping the stirred product into a sand mill by a peristaltic pump for liquid phase grinding for 1h-6h to form an emulsion; Step 2: Add a coating agent whose mass is 10% to 100% of the mass of the carbon powder to the emulsion, wherein the coating agent is one or more of petroleum asphalt, coal asphalt or emulsified asphalt, grind the mixture of the emulsion and the coating agent in liquid phase for 0.5h to 3h, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product in a nitrogen atmosphere tube furnace at 300° C.-600° C. for 0.5 h-4 h to form a spherical concave carbon powder; Step 4: The spherical concave carbon powder and the alkali are mixed in a mass ratio of 1:1-4, and then placed in a tubular furnace in a nitrogen atmosphere and calcined at 700°C-900°C for 0.5h-4h, pickled with 1mol / L hydrochloric acid, washed with ethanol, washed with deionized water for multiple times until neutral, and dried in an oven to obtain a carbon skeleton, wherein the alkali is sodium hydroxide or potassium hydroxide; Step 5: placing the carbon skeleton in a fluidized bed, introducing a silicon source gas at a flow rate of 0.5 L / min-5 L / min into the fluidized bed, and keeping the temperature at 400° C.-700° C. for 1 h-6 h, wherein the silicon source gas is one of monosilane, disilane, trisilane or alkyl halide; Step 6: Switch the silicon source gas to an organic source gas with a flow rate of 0.5L / min-5L / min, and keep it at 400℃-800℃ for 2h-6h to obtain a rate-type silicon-carbon material. The organic source gas is one of acetylene, propane, cyclohexane, methane or benzene.

[0021] The present invention also provides a rate-type silicon-carbon material, which is prepared by the above-mentioned method for preparing the rate-type silicon-carbon material.

[0022] The present invention also provides the use of the rate-modifying silicon-carbon material as a negative electrode of a lithium-ion battery.

[0023] The primary particle refinement in the present invention specifically refers to grinding the carbon powder crushed by the air flow mill to the nanometer level by a sand mill, and controlling the size of the secondary granulation particles by adjusting the final size of the refined particles; the secondary granulation uses the primary refined particles as the nucleation source, and forms particles with special morphology and meeting the size requirements with the help of a coating agent during the spray granulation process, and then forms a stable particle structure through calcination; through primary particle refinement and secondary granulation spheroidization, a round carbon skeleton is prepared at a relatively low cost; the dispersant plays a role in inhibiting particle agglomeration during the particle grinding and refinement process, so that the carbon powder can be ground into fine and dispersed particles with the fastest efficiency. The coating agent has the characteristics of low-temperature viscosity and high-temperature softening. During the secondary granulation spraying process, the particles are agglomerated into balls and softened at high temperature to form a dense coating. The alkali reacts chemically with the intermediate product at high temperature to activate the pores. The rate-type silicon-carbon material prepared by the present invention has a smooth and round surface, and some particles are concave. Electrons are not easy to gather during the charge and discharge process, which not only avoids the tip discharge phenomenon, but also improves the compaction density of the material, increases the contact area between the active material particles, and reduces the force between the particles in contact with each other. The rolled particles are not easy to break, which is beneficial to the rate cycle and safety and stability of the battery.

[0024] Embodiment 1: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: Pitch coke is crushed into carbon powder with a particle size of 5 μm by a jet mill, 50 g of carbon powder and 2.5 g of PVP are mixed and added to 350 g of ethanol for stirring, and the stirred product is pumped into a sand mill for liquid phase grinding for 3 hours by a peristaltic pump to form an emulsion; Step 2: Add 50 g of emulsified asphalt to the emulsion, grind for 2 hours, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product at 550° C. for 3 h in a nitrogen atmosphere tube furnace to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 40 g of potassium hydroxide were mixed in a mortar and placed in a tube furnace in a nitrogen atmosphere and calcined at 800° C. for 2 h, followed by pickling with 1 mol / L hydrochloric acid, washing with ethanol, washing with deionized water 6 times until neutral, and drying in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing monosilane gas at a flow rate of 0.5 L / min into the fluidized bed, and keeping the temperature at 600° C. for 4 h; Step 6: Switch the monosilane gas to acetylene gas with a flow rate of 3 L / min, keep it at 550°C for 2 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0025] Embodiment 2: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: crush the bamboo charcoal into charcoal powder with a particle size of 2 μm by a jet mill, mix 50 g charcoal powder and 0.5 g PVP and add them into 1010 g ethanol for stirring, and pump the stirred product into a sand mill for liquid phase grinding for 1 hour by a peristaltic pump to form an emulsion; Step 2: Add 5 g of petroleum asphalt to the emulsion, grind for 0.5 h, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product in a nitrogen atmosphere tube furnace at 300° C. for 0.5 h to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 20 g of potassium hydroxide were mixed in a mortar and placed in a tubular furnace in a nitrogen atmosphere and calcined at 700° C. for 0.5 h, followed by pickling with 1 mol / L hydrochloric acid, washing with ethanol, washing with deionized water 8 times until neutral, and drying in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing monosilane gas at a flow rate of 2 L / min into the fluidized bed, and keeping the temperature at 600° C. for 4 h; Step 6: Switch the monosilane gas to methane gas with a flow rate of 3 L / min, keep it at 550°C for 2 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0026] Embodiment 3: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: crush bamboo charcoal into charcoal powder with a particle size of 15 μm by a jet mill, mix 50 g charcoal powder and 5 g oleic acid, add them into 184 g ethanol and stir, and pump the stirred product into a sand mill by a peristaltic pump for liquid phase grinding for 1 hour to form an emulsion; Step 2: Add 31 g of petroleum asphalt to the emulsion, grind for 0.5 h, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product at 600° C. for 4 h in a nitrogen atmosphere tube furnace to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 80 g of sodium hydroxide were mixed in a mortar and placed in a tubular furnace in a nitrogen atmosphere and calcined at 900 ° C for 4 h, washed with 1 mol / L hydrochloric acid, washed with ethanol, washed with deionized water 5 times until neutral, and dried in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing trisilane gas at a flow rate of 2 L / min into the fluidized bed, and keeping the temperature at 600° C. for 4 h; Step 6: Switch the trisilane gas to acetylene gas with a flow rate of 3 L / min, keep it at 550°C for 2 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0027] Embodiment 4: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: Phenolic resin carbon is crushed into carbon powder with a particle size of 8 μm by a jet mill, 50 g of carbon powder is mixed with 3 g of oleic acid and 1 g of PVP, and then added into 216 g of ethanol for stirring, and the stirred product is pumped into a sand mill for liquid phase grinding for 4 hours by a peristaltic pump to form an emulsion; Step 2: Add 50 g of coal tar into the emulsion, grind for 3 hours, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product at 420° C. for 3.5 h in a nitrogen atmosphere tube furnace to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 35 g of sodium hydroxide were mixed in a mortar, calcined at 850° C. for 3 h in a tube furnace in a nitrogen atmosphere, pickled with 1 mol / L hydrochloric acid, washed with ethanol, washed with deionized water 4 times until neutral, and dried in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing disilane gas at a flow rate of 4 L / min into the fluidized bed, and keeping the temperature at 580° C. for 6 h; Step 6: Switch the disilane gas to acetylene gas with a flow rate of 2.5 L / min, keep it at 650°C for 3 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0028] Embodiment 5: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: Pulverize the asphalt coke into carbon powder with a particle size of 5 μm by a jet mill, mix 50 g of carbon powder and 3 g of PVP, add them into 350 g of ethanol and stir, and pump the stirred product into a sand mill by a peristaltic pump for liquid phase grinding for 3 hours to form an emulsion; Step 2: Add 50 g of emulsified asphalt to the emulsion, grind for 2 hours, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product at 550° C. for 3 h in a nitrogen atmosphere tube furnace to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 40 g of sodium hydroxide were mixed in a mortar and placed in a nitrogen atmosphere tube furnace at 800 ° C. for 2 h, pickled with 1 mol / L hydrochloric acid, washed with ethanol, washed with deionized water 6 times until neutral, and dried in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing monosilane gas at a flow rate of 0.5 L / min into the fluidized bed, and keeping the temperature at 400° C. for 1 h; Step 6: Switch the monosilane gas to cyclohexane gas with a flow rate of 0.5 L / min, keep it at 400°C for 2 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0029] Embodiment 6: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: Pitch coke is crushed into carbon powder with a particle size of 6 μm by a jet mill, 50 g of carbon powder and 2.5 g of ricinoleic acid are mixed and added to 350 g of ethanol for stirring, and the stirred product is pumped into a sand mill for liquid phase grinding for 3 hours by a peristaltic pump to form an emulsion; Step 2: Add 50 g of emulsified asphalt to the emulsion, grind for 2 hours, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product at 500° C. for 3 h in a tubular furnace under a nitrogen atmosphere to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 40 g of potassium hydroxide were mixed in a mortar and calcined at 800 ° C for 2 h in a tube furnace in a nitrogen atmosphere, pickled with 1 mol / L hydrochloric acid, washed with ethanol, washed with deionized water 7 times until neutral, and dried in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing halogenated alkane gas at a flow rate of 5 L / min into the fluidized bed, and keeping the temperature at 700° C. for 6 h; Step 6: Switch the halogenated hydrocarbon gas to acetylene gas with a flow rate of 5 L / min, keep it at 800°C for 2 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0030] Embodiment 7: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: crush the bamboo charcoal into charcoal powder with a particle size of 10 μm by a jet mill, mix 50 g of charcoal powder and 2 g of PVP, add them into 350 g of ethanol and stir, and pump the stirred product into a sand mill through a peristaltic pump for liquid phase grinding for 1 hour to form an emulsion; Step 2: Add 34 g of emulsified asphalt to the emulsion, grind for 0.5 h, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product in a nitrogen atmosphere tube furnace at 300° C. for 1.5 h to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 30 g of potassium hydroxide were mixed in a mortar and placed in a tubular furnace in a nitrogen atmosphere and calcined at 700° C. for 2 h, followed by pickling with 1 mol / L hydrochloric acid, washing with ethanol, washing with deionized water 5 times until neutral, and drying in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing monosilane gas at a flow rate of 2 L / min into the fluidized bed, and keeping the temperature at 600° C. for 4 h; Step 6: Switch the monosilane gas to acetylene gas with a flow rate of 3 L / min, keep it at 550°C for 2 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0031] Embodiment 8: A method for preparing a rate-type silicon-carbon material comprises the following steps: Step 1: Phenolic resin carbon is crushed into carbon powder with a particle size of 8 μm by a jet mill, 50 g of carbon powder is mixed with 3 g of octanoic acid and 1 g of stearic acid, and then added to 216 g of ethanol for stirring, and the stirred product is pumped into a sand mill for liquid phase grinding for 4 hours by a peristaltic pump to form an emulsion; Step 2: Add 50 g of coal tar into the emulsion, grind for 3 hours, and then spray granulate to obtain an intermediate product; Step 3: calcining the intermediate product at 420° C. for 3.5 h in a nitrogen atmosphere tube furnace to form a spherical concave carbon powder; Step 4: 20 g of spherical concave carbon powder and 35 g of sodium hydroxide were mixed in a mortar, calcined at 850° C. for 3 h in a tube furnace in a nitrogen atmosphere, pickled with 1 mol / L hydrochloric acid, washed with ethanol, washed with deionized water 4 times until neutral, and dried in an oven to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing trisilane gas at a flow rate of 4 L / min into the fluidized bed, and keeping the temperature at 580° C. for 6 h; Step 6: Switch the trisilane gas to methyl ene gas with a flow rate of 2.5 L / min, keep it at 650°C for 3 hours, and obtain a rate-type silicon-carbon negative electrode material.

[0032] The rate-type silicon-carbon materials provided in Examples 1-8, the existing coconut shell vapor phase silicon-carbon, and the existing super carbon vapor phase silicon-carbon were tested for their electrical performance, and the results are shown in Table 1: Table 1 Silicon-carbon negative electrode material buckling performance test table

[0033] Referring to Table 1, the rate-type silicon-carbon material prepared by the present invention has a good capacity retention rate regardless of the capacity, which proves its good rate performance. Although coconut shell gas phase silicon carbon and super carbon gas phase silicon carbon can achieve a higher reversible capacity, the capacity retention rate decreases rapidly with the increase of current density, and the rate performance is poor. The capacity retention rate at 0.5C, 1C, and 2C charging rates is less than that of the rate-type silicon-carbon material prepared by the present invention. Figure 4 After assembling full batteries of Example 1, coconut shell fumed silicon carbon, and super carbon fumed silicon carbon, the cycle tests were carried out at 0.5C discharge rate and 1C charge rate. In contrast, Example 1 has a better capacity retention rate, and still has a reversible capacity of more than 95% after 1000 cycles. Figure 5The comparison shows that the rate-type silicon-carbon material prepared by the present invention can still have a capacity retention rate of more than 97% at a charging rate of 7C, proving that it has more excellent cycle stability and fast charging performance.

[0034] contrast Figure 1 , Figure 2 , Figure 3 By comparison, it can be seen that both coconut shell gas phase silicon carbon and super carbon gas phase silicon carbon maintain the morphology of the original particles, the particles have irregular morphology, more fine powder, and sharp edges and corners. The surface of the rate-type silicon carbon material particles prepared by the present invention is smooth and flat, with a special round and ring-shaped morphology, and the particles have no edges and corners.

Claims

1. A method for preparing a rate-type silicon-carbon material, characterized in that: The following steps are involved: Step 1: crushing the carbon precursor into carbon powder, mixing the carbon powder and the dispersant, adding them into ethanol, stirring, and grinding for the first time to form an emulsion; Step 2: adding a coating agent to the emulsion for a second grinding and spray granulation to obtain an intermediate product; Step 3: calcining the intermediate product for the first time to form spherical concave carbon powder; Step 4: Mix the spherical concave carbon powder and alkali, perform a second calcination, wash, and dry to obtain a carbon skeleton; Step 5: placing the carbon skeleton in a fluidized bed, introducing silicon source gas into the fluidized bed, and keeping the temperature at 400° C.-700° C. for 1 h-6 h; Step 6: Switch the silicon source gas to an organic source gas, keep the temperature at 400°C-800°C for 2h-6h, and obtain a rate-type silicon-carbon material.

2. The method for preparing a rate-type silicon-carbon material according to claim 1, characterized in that: The first grinding method is to pump the stirred product into a sand mill through a peristaltic pump for liquid phase grinding, and the second grinding method is to grind the mixture of the emulsion and the coating agent in a sand mill for liquid phase grinding.

3. The method for preparing a rate-type silicon-carbon material according to claim 1, characterized in that: The carbon precursor is one of biomass carbon, resin carbon or coke, and the pulverizing method is to pulverize the carbon precursor into carbon powder with a particle size of 2μm-15μm by a jet mill. The dispersant is one or more of stearic acid, PVP, oleic acid, ricinoleic acid or octanoic acid. The carbon powder and the dispersant are mixed in a mass ratio of 10-100:

1. After the carbon powder and the dispersant are mixed, they are added to ethanol so that the mass proportion of the carbon powder is 5%-30%, and the time of the first grinding is 1h-6h.

4. The method for preparing a rate-type silicon-carbon material according to any one of claims 1 to 3, characterized in that: The coating agent is one or more of petroleum asphalt, coal asphalt or emulsified asphalt. The mass of the added coating agent is 10%-100% of the mass of the carbon powder. The time of the second grinding is 0.5h-3h.

5. The method for preparing a rate-type silicon-carbon material according to claim 1, characterized in that: The first calcination and the second calcination are both carried out in a tubular furnace in a nitrogen atmosphere. The first calcination is carried out at 300° C.-600° C. for 0.5 h-4 h, and the second calcination is carried out at 700° C.-900° C. for 0.5 h-4 h.

6. The method for preparing a rate-type silicon-carbon material according to claim 1 or 5, characterized in that: The alkali is sodium hydroxide or potassium hydroxide, the intermediate product and the alkali are mixed in a mass ratio of 1:1-4, the washing method is acid washing with 1 mol / L hydrochloric acid, ethanol washing, and multiple deionized water washings until neutrality, and the drying method is drying in an oven.

7. The method for preparing a rate-type silicon-carbon material according to claim 6, characterized in that: The silicon source gas is one of monosilane, disilane, trisilane or alkyl halide, and the flow rate of the silicon source gas is 0.5 L / min-5 L / min.

8. The method for preparing a rate-type silicon-carbon material according to claim 1 or 7, characterized in that: The organic gas source is one of acetylene, propane, cyclohexane, methane or benzene, and the flow rate of the organic gas source is 0.5L / min-5L / min.

9. A rate-type silicon-carbon material, characterized in that: The rate-type silicon-carbon material is prepared by the method for preparing the rate-type silicon-carbon material according to any one of claims 1 to 8.

10. Use of the rate-modifying silicon-carbon material according to claim 9 as a negative electrode of a lithium-ion battery.

Citation Information

Cited By

  • Silicon-carbon material and preparation method thereof, porous carbon substrate, negative electrode material and battery

    CN119812286A